2011
DOI: 10.1557/opl.2011.1227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultra-thin Layer Fabricated by Wet-process as a Pore-Seal for Porous Low-k Films

Abstract: We focused on detailed evaluations of properties of the ultra-thin pore-seal layer (< 3 nmthick), such as Cu diffusion barrier property and thermal stability. Cu diffusion into dense thermal silica and porous silica low-k which are covered with the pore seal layer was evaluated using metal-insulator-semiconductor (MIS) capacitors under bias thermal stress (BTS). Triangular voltage sweep (TVS) measurement shows that the ultra-thin layer on dense thermal silica suppresses the drift of Cu ions. The Time-Dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…[16] It was also reported that molecular structure of pore sealant determines the pore seal performance. [17] In order to apply the pore seal layer in future ULSI Cu interconnect, the understanding how metals or the species of plasma is blocked by the pore seal layer is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…[16] It was also reported that molecular structure of pore sealant determines the pore seal performance. [17] In order to apply the pore seal layer in future ULSI Cu interconnect, the understanding how metals or the species of plasma is blocked by the pore seal layer is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…[10] We discovered the phenomena that the ultra-thin layer suppresses the diffusion of PVD-Cu by evaluations of cross-sectional TEM and BTS measurement. [11] The understanding of mechanisms playing a role in sealing the surfaces of porous dielectrics is fundamentally important for an effective integration of new materials in the interconnect processing. In this paper, we prepared various types of pore sealants and porous low-k and studied the relationship between structure of pore sealants and pore size of porous low-k using toluene based ellipsometric porosimetry (EP) measurements.…”
Section: Introductionmentioning
confidence: 99%